THE COSTS FOR ENTREPRENEURS EMPLOYING PEOPLE WITH DISABILITIES IN POLAND (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
lang="X-NONE">The article presents the costs that are incurred to support the employment of people with disabilities in the Polish system of vocational rehabilitation and employment. Employment support system includes the following elements: subsidies to salaries of disabled employees, the refund of additional costs of employing disabled workers, assistance in adaptation and supplying equipment for the workplace and the refund of salary of the employee helping a person with a disability at work. All this generates high financial costs of the system. This is mainly due to the very nature of the disability, which generates additional costs. Without adequate support people with disabilities can not cope in the labour market, and employers will not be interested in employing such workers. Note, however, that the balance of costs and benefits of professional activation of the disabled takes a positive value most often. Working person with disability is simply "cheaper" than the unemployed, who gets a pension, if only because they pay income tax on their earnings, buy more products and therefore pay more VAT, pay rent for their apartment and what is important they are involved in social life. In addition, the economic analysis of the costs incurred in the system allows to look at the facts and phenomena occurring and to determine their causes, particularly the low activity of people with disabilities. Furthermore, on the basis of cost, especially when compared with the effects, one can make an initial assessment of the system.